2006
DOI: 10.1098/rspb.2006.3731
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for chick discrimination without recognition in a brood parasite host

Abstract: Recognition is considered a critical basis for discriminatory behaviours in animals. Theoretically, recognition and discrimination of parasitic chicks are not predicted to evolve in hosts of brood parasitic birds that evict nest-mates. Yet, an earlier study showed that host reed warblers (Acrocephalus scirpaceus) of an evicting parasite, the common cuckoo (Cuculus canorus), can avoid the costs of prolonged care for unrelated young by deserting the cuckoo chick before it fledges. Desertion was not based on spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 29 publications
1
86
0
Order By: Relevance
“…Additionally, we used lower-resolution recordings from infrared microcameras (CCD Bird Box Camera 420TVL; SpyCameraCCTV, Bristol, UK) located inside nest boxes; each microcamera was connected to a digital video-recorder (Wireless 2.4 GHz 1 Channel D1 Mini DVR Recorder; SpyCameraCCTV) hidden in an underground box below the nest. Microcameras were primarily used to determine the exact time of fledging of host and parasitic nestlings, as they allowed us to record the brood undisturbed for several days without the need to check the nest in person, which may cause premature fledging (Grim 2007b). However, we also took advantage of these microcamera recordings to determine dietary items, although necessarily at a lower level of taxonomic detail (invertebrate, vertebrate, and plant).…”
Section: Video-recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we used lower-resolution recordings from infrared microcameras (CCD Bird Box Camera 420TVL; SpyCameraCCTV, Bristol, UK) located inside nest boxes; each microcamera was connected to a digital video-recorder (Wireless 2.4 GHz 1 Channel D1 Mini DVR Recorder; SpyCameraCCTV) hidden in an underground box below the nest. Microcameras were primarily used to determine the exact time of fledging of host and parasitic nestlings, as they allowed us to record the brood undisturbed for several days without the need to check the nest in person, which may cause premature fledging (Grim 2007b). However, we also took advantage of these microcamera recordings to determine dietary items, although necessarily at a lower level of taxonomic detail (invertebrate, vertebrate, and plant).…”
Section: Video-recordingmentioning
confidence: 99%
“…Video-recordings confirmed that cuckoo nestlings did not try to fledge before we removed the nails. Third, fledging time was primarily determined from longterm microcamera recordings, which started a day or 2 before the expected fledging date for a particular nest and thus eliminated the necessity of repeated nest checks by a human observer during the period shortly before nestlings fledge when human nest checks may trigger premature fledging (see also Grim 2007b).…”
Section: Study Area and General Proceduresmentioning
confidence: 99%
“…For example, Acrocephalus hosts increase mobbing behaviour at the nest when the risk of parasitism is high [13]. But when brood parasite risk is low, hosts accept more foreign eggs into their nest, thereby lowering the rejection threshold for eggs and chicks [12,14]. Here, we test whether incubating female fairy-wrens increase their incubation call rate when they hear the broadcast of a cuckoo near their nest.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, cuckoo parasitism severely reduces the host's fitness [2,3], typically because the parasitic chick evicts host eggs and nest-mates [4,5]. This results in coevolutionary arms-races [6] of morphological, physiological and cognitive adaptations and counter-adaptations between parasites and hosts; hosts recognize and avoid parasitism and parasites reduce or circumvent rejection by hosts [1,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%